The Relationship Between Anxiety Level and Quality of Life in Hypertensive Patients at Kalijati Subang Health Center - Mastria Tamara Dewi; Habsyah Saparidah Agustina; Rosiah Rosiah (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Hypertension is a cardiovascular disease and chronic medical condition in which blood pressure increases with systolic 140 mmHg and diastolic 90 mmHg. The longer the patient suffers from hypertension, it will lead to complications such as heart failure, kidney failure, and stroke and also cause physical symptoms such as psychological problems, namely anxiety, which can affect a person's quality of life. The purpose of this study was to determine the relationship between anxiety levels and quality of life in hypertensive patients at Kalijati Subang Health Center. The research method used is quantitative. The sampling technique in this study used purposive sampling and obtained a total sample of 91 people. Data analysis in this study used bivariate analysis with the Spearman RankTest. The study's results obtained a p-value of 0.001 (<0.05), which can be interpreted as a relationship between anxiety and quality of life in hypertensive patients at Piskesmas Kalijati Subang. The conclusion that can be explained is that the level of anxiety is related to the quality of life in hypertensive patients at the Kalijati Subang Health Center. From this study, it is hoped that puskesmas can maintain in intervening with patients who experience anxiety so that the quality of life in hypertensive patients is getting better.